Optimal surgical population for cervical lymph node dissection in PTC - Wang, Yongkun; Wu, Zhen; Yan, Jinqiang; Yao, Yumin; Han, Lin (Frontiers in Oncology, 2024)
Objective: There is still controversy about whether cervical lymph node dissection should be performed in surgical treatment of PTC. Based on the data of thyroid cancer patients from Liaocheng People's Hospital from 2015 to 2018, this study focused on appropriate indications for cervical lymph node dissection surgery. Methods: The clinical and pathological data of patients with initial treatment of PTC in thyroid surgery department from 2015 to 2018 were collected. In all cases, 1001 patients underwent total thyroidectomy + central lymph node dissection, and 1107 patients underwent total thyroidectomy + central + cervical lymph node dissection. Results: The average metastasis rate of all cases was 57.23%, and even the metastasis rate of PTMC was as high as 48.97%. The total metastasis rate of central and lateral cervical lymph nodes was 74.44%, and the cervical lymph nodes were present in 49.32% of the metastatic cases. In 55.56% of the cases, the tumor diameter was more than 1 cm, and the metastasis rate of cervical lateral area was 56%. With the increase of tumor diameter, the cervical metastasis rate increased from 22.54% to 73.33%. Conclusion: The metastasis rate of PTC is more than 50%, and nearly half of them have cervical metastasis, especially in patients with high risk factors. We observed that PTC 1 cm or greater has significant rates of metastasis.